1987
DOI: 10.1159/000138313
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor of Adult Rabbit Lung

Abstract: Properties of progestin binding sites in adult male rabbit lung cytosol were analyzed using [3H] promegestone ([3H]R5020). At concentrations of 0.05–10 nM, [3H]R5020 bound to two saturable sites with differing affinities: a high affinity site (Kd = 0.34 nM, Bmax = 57 fmol/mg protein) and a moderate affinity site (Kd = 60 nM, Bmax = 540 fmol/mg protein). [3H]R5020 binding, under conditions selected to favor binding to the high affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…More specifically, our results strongly suggest that regulation of PRA protein expression is mediated by the actions of GR in response to glucocorticoids. The presence of PR in lungs of different species (Giannopoulos et al 1982, Moser & Daxenbichler 1982, Bullock et al 1987, Nielsen et al 1987, Camacho-Arroyo et al 1994, Pasanen et al 1997, Beyer et al 2003, is not surprising. However, our experiments do not provide evidence for the existence of PRB in mouse lung.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…More specifically, our results strongly suggest that regulation of PRA protein expression is mediated by the actions of GR in response to glucocorticoids. The presence of PR in lungs of different species (Giannopoulos et al 1982, Moser & Daxenbichler 1982, Bullock et al 1987, Nielsen et al 1987, Camacho-Arroyo et al 1994, Pasanen et al 1997, Beyer et al 2003, is not surprising. However, our experiments do not provide evidence for the existence of PRB in mouse lung.…”
Section: Discussionmentioning
confidence: 97%
“…asthma and cancer) (Milne 1979, Haggerty et al 2003, Ishibashi et al 2005, the regulation and cellular distribution of PR protein isoforms in lung remain largely unknown. Previous studies have shown that PR mRNAs and proteins are found in rabbit (Giannopoulos et al 1982, Bullock et al 1987, Nielsen et al 1987, Camacho-Arroyo et al 1994, rodent (Moser & Daxenbichler 1982, Beyer et al 2003, and chicken (Pasanen et al 1997) lungs. In the present study, we sought to initially establish the presence of PR isoforms in mouse lung using reverse transcriptase (RT)-PCR and Western blotting analyses and on finding that PRA mRNA and protein were specifically expressed in mouse lung, we examined the possibility of regulation of PRA protein expression in mice during postnatal growth and development.…”
Section: Introductionmentioning
confidence: 96%